PsAPASH: a rare and recent autoinflammatory syndrome associated with hidradenitis suppurativa, - Raissa de Lima Gadelha; Renata da Silveira Rodrigues Paiva; Esther Bastos Palitot; Joanne Elizabeth Ferraz da Costa (Sociedade Brasileira de Dermatologia, 2020)
Abstract Hidradenitis suppurativa is a chronic inflammatory skin disease, which affects 1% of the population, being more common in young, obese and smokers, and mainly affects armpits and groin, with formation of pustules, nodules, abscesses, scars and fistulas. Recently, its association with other autoimmune diseases such as psoriasis, psoriatic arthritis, pyoderma gangrenosum, pyogenic arthritis and ulcerative colitis have been reported. These associated forms are usually resistant to standard treatment, with immunobiologicals as promising therapy. The case of a rare form of association is reported, with only one case previously described in the literature: psoriasis arthritis, pyoderma gangrenosum, acne and hidradenitis suppurativa.